A method for preparing polymerized iron and aluminum from acidic etching solution
By adopting two-stage replacement method and catalytic oxidation steps in the treatment of acid etching liquid, liquid polymer aluminum chloride PAFC is obtained, which solves the problems of low treatment efficiency and waste of resources in the prior art, and achieves efficient copper recovery and sewage treatment effects.
Patent Information
- Application Number
- CN202411991954.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
The prior art produces a large amount of industrial waste liquid when treating acid etching liquid, which has high energy consumption for wastewater treatment, complex process and low treatment efficiency, and cannot effectively utilize acid etching liquid, resulting in waste of resources and environmental pollution.
The copper ions in the acid etching liquid were replaced by a two-stage replacement method, and then liquid polymer aluminum ferrochloride PAFC was prepared through catalytic oxidation and post-treatment steps to realize the resource utilization of the acid etching liquid.
The copper in the acid etching solution is effectively recovered, with the copper recovery rate greater than 99%, and the purity of the product sponge copper is greater than 93%. The prepared aluminum-ferrous chloride solution can be used for wastewater removal, improving treatment efficiency and environmental benefits.
Smart Images

Figure BDA0005223834330000081 
Figure BDA0005223834330000082 
Figure BDA0005223834330000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of resource recovery and utilization of acid etching liquid, and in particular to a method for preparing polymerized iron and aluminum from acid etching liquid. Background Art
[0002] With the rapid development of modern information industry and electronic industry, the demand for high-quality printed circuit boards is increasing. In recent years, many printed circuit board processing enterprises have been built and put into production, and circuit boards have also developed from single-sided boards to double-sided boards and multi-layer boards to meet the needs of domestic information and electronic industries. Acidic copper chloride etching solution is often used in the process of printed circuit board processing, which produces a large amount of Cu-containing products during etching and subsequent cleaning. 2+ Acidic etching solution. Acidic etching solution is highly toxic and contains high levels of organic matter and heavy metals. Discharging untreated acidic etching solution will not only cause a serious waste of resources, but also increase the difficulty and cost of subsequent sewage treatment, causing environmental pollution.
[0003] At present, commonly used acid etching liquid treatment process methods include: (i) pretreatment-precipitation-filtration method (CN104313583A discloses a precipitant for recycling and reusing acid etching waste liquid and its treatment method); (ii) extraction method (CN114703377A discloses a method for extracting copper from acid etching waste liquid); (iii) neutralization method (such as) and (iv) acid replacement method (such as CN101899665A discloses a method for recovering copper from acid copper chloride etching liquid, CN102912352A discloses a method for recovering and reusing acid copper etching waste liquid. However, the prior art still has the following technical problems: (1) The prior art will generate a large amount of industrial waste liquid, with poor environmental benefits; the energy consumption in the sewage treatment process is high; (2) The prior art process is complex and the treatment efficiency of the acid etching liquid is low; (3) It is impossible to recycle a large amount of acid etching liquid, resulting in waste.
[0004] In view of this, developing a method for preparing polymerized iron aluminum from acidic etching liquid can not only effectively make up for the shortcomings of the existing technology, but also promote the resource utilization of acidic etching liquid, which is of great significance for achieving the unity of environmental benefits and economic benefits in the process of acidic etching liquid treatment. Summary of the invention
[0005] The present invention aims to provide a method for preparing polymerized iron and aluminum from an acidic etching solution, so as to solve the technical problems that a large amount of industrial waste liquid is generated in the prior art for treating the acidic etching solution, and the energy consumption for sewage treatment is high.
[0006] To achieve the above object, the present invention adopts the following technical scheme: a method for preparing polymerized iron aluminum from an acidic etching solution, comprising the following steps:
[0007] Step 1, two-stage replacement: aluminum and iron are added to the acidic etching solution in batches to perform two-stage replacement of copper ions in the acidic etching solution to obtain a mixed solution of sponge copper and ferrous chloride and aluminum chloride;
[0008] Step 2, catalytic oxidation: adding a catalyst to the mixed solution, introducing oxygen, oxidizing the divalent iron ions in the mixed solution into trivalent iron ions, and obtaining a reaction solution;
[0009] Step 3, post-treatment: The reaction solution is subjected to hydrolysis treatment, polymerization treatment, and aging treatment to obtain liquid polyaluminium ferric chloride PAFC.
[0010] Preferably, as an improvement, in step one, the two-stage replacement is as follows: according to the copper ion content in the acidic etching solution, iron powder with a copper ion content of 1.1 to 1.2 times is added during the first-stage replacement, and after the addition is completed, the sponge copper is collected after replacement at 60 to 80° C. for 7 to 8 hours; aluminum with a copper ion content of 1.1 to 1.2 times is added during the second-stage replacement, and the sponge copper is collected after replacement for 2 to 3 hours, and the remaining filtrate is a mixed solution of FeCl2 and AlCl3.
[0011] Beneficial effect: This solution adopts the above solution, which is convenient for batch processing of 12m 3 When using an acidic etching solution, the reaction rate can be guaranteed while side reactions can be avoided. The applicant has found through long-term experiments that when a small batch of acidic etching solution (200-400 ml) is processed, the primary replacement only takes 1 hour to complete. However, when processing large quantities of acidic etching solution, not only is the reaction time prolonged, but also the temperature rises rapidly when the reaction is intense, which may cause salt decomposition and affect the reaction effect; and if the reaction temperature is too low, the dissolution rate will be slow, reducing production efficiency. Therefore, controlling the reaction temperature during the primary replacement at 60°C to 80°C can ensure the smooth progress of the reaction while avoiding unnecessary side reactions.
[0012] Preferably, in the two-stage replacement process, the amount of iron powder and aluminum flakes added is such that the molar mass ratio of Fe to Al in the mixed solution after replacement is 4.5 to 5.5:1.
[0013] Preferably, as an improvement, in step 2, the catalyst is sodium nitrite, and the amount of catalyst added is 3‰; the oxidant is oxygen.
[0014] Preferably, as an improvement, the pressure of the catalytic oxidation is 0.02-0.03 MPa, the temperature is controlled within 75° C., and the reaction time is 3-4 h.
[0015] Beneficial effect: This scheme adopts the above scheme to ensure continuous, rapid and sufficient oxidation to obtain ferric chloride solution. The applicant found through long-term experiments that because the scheme adopts catalytic oxidation equipment, the oxidation rate mainly depends on the air intake of the ejector. If the set catalytic oxidation pressure is too low, the reaction speed will be too fast in the middle of the reaction, resulting in excessive oxygen consumption, and the pressure will drop too fast or even negative pressure or vacuum will occur. In this case, the risk of tank rupture will increase, and safety hazards will increase; step back, even if the one-way air intake valve set by the equipment can avoid equipment damage, the one-way air intake valve inhales air, and air entering the equipment will also reduce the reaction efficiency and affect the reaction effect. If the set catalytic oxidation pressure is too high, excess oxygen needs to be discharged after the reaction is completed, resulting in oxygen waste and increased costs. The catalytic oxidation reaction is an exothermic reaction, and the reaction can be started under normal temperature conditions. As the reaction releases heat, the temperature in the tank will gradually rise. By controlling the reaction temperature within 75°C, this scheme can effectively avoid high temperature damage to the equipment, and ensure that the catalytic oxidation reaction proceeds quickly, thereby improving production efficiency.
[0016] Preferably, as an improvement, in step 2, the catalytic oxidation can also be replaced by conventional oxidation, wherein the conventional oxidation is to add hydrochloric acid in combination to the mixed solution under room temperature and stirring to adjust the free acid and Cl-Fe ratio of the mixed solution, add sodium chlorate or hydrogen peroxide as an oxidant, oxidize the divalent iron ions in the mixed solution into trivalent iron ions, and obtain a reaction solution.
[0017] Preferably, as an improvement, the amount of hydrochloric acid added is such that the molar mass ratio of Cl to Fe in the mixed solution is 0.7 to 0.9:1.
[0018] Preferably, as an improvement, the amount of sodium chlorate added is such that the sodium chlorate and Fe 2+ The molar mass ratio is 0.336:1.
[0019] This solution achieves the following technical effects:
[0020] (1) The acidic etching solution of this scheme adopts the steps of aluminum-iron two-stage replacement of copper ions, oxidation, aging, etc. to prepare PAFC and recover copper blocks, with iron: aluminum = 4.5-5.5: 1, hydrochloric acid: iron = 0.7-0.9: sodium chlorate: iron = 0.336: alkalinity = 0.5, and the PAFC detection index meets the GB5359-2018 standard; among which, the copper recovery rate is greater than 99%, and the purity of the product sponge copper is greater than 93% (dry basis).
[0021] (2) When the aluminum ferric chloride solution prepared in this scheme is used for flocculation experiments, the dosage is 0.5-1.0% and the pH is 6-9. The flocculated flocs of the suspension, waste emulsion, sewage in the regulating tank, and waste paint water are large and compact, the sedimentation speed is fast, the effluent is clear, and the sedimentation effect is good. It can be used for sewage deturbidity removal. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a front view of the catalytic oxidation device in an embodiment of the present invention.
[0023] Figure 2 It is a top view of the catalytic oxidation device in an embodiment of the present invention.
[0024] Figure 3 It is a schematic diagram of the connection structure between the ejector and the acceleration reactor of the catalytic oxidation device in an embodiment of the present invention.
[0025] Figure 4 This is a state diagram of the polymerized iron alumina prepared by the method for preparing polymerized iron alumina from an acidic etching solution in Example 1 of the present invention (from left to right, they are PAFC(1), PAFC(2), and PAFC(3)).
[0026] Figure 5 This is a state diagram of the polyaluminium ferric chloride flocculation experiment in Experimental Example 1 of the present invention (from left to right: prepared suspension, waste emulsion, and flocculation and precipitation of sewage in the regulating tank).
[0027] Figure 6 This is a diagram of the PAFC (1) flocculation experiment state in Experimental Example 1 of the present invention (two pictures form a group, the left group is the configuration of the suspension and waste paint water in a stirring state; the right group is the configuration of the suspension and waste paint water after standing).
[0028] Figure 7 This is a state diagram of the PAFC (2) flocculation experiment in Experimental Example 1 of the present invention (two pictures form a group, the left group is the configuration of the suspension and waste paint water in a stirring state; the right group is the configuration of the suspension and waste paint water after standing). DETAILED DESCRIPTION
[0029] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto. Unless otherwise specified, the technical means used in the following examples and experimental examples are conventional means well known to those skilled in the art, and the materials, reagents, etc. used can be obtained from commercial sources.
[0030] The marks in the drawings of the specification include: circulating pump 1, feed pipe 2, cylinder 3, discharge pipe 4, ejector 5, connecting pipe 6, manhole 7, oxygen inlet hole 8, auxiliary material hole 9, ejector installation port 10, liquid material feed port 11, suction hole 12, observation mirror 13, remote thermometer 14, solid material addition port 15, bursting disc 16, pressure relief valve 17, tail gas hole 18, liquid alkali and tap water inlet hole 19, remote pressure gauge 20, graphite inlet 21, graphite outlet 22, one-way suction valve 23.
[0031] Example 1
[0032] This solution provides a method for preparing polymerized iron aluminum from an acidic etching solution, comprising the following steps:
[0033] Step 1, two-stage replacement: Take a certain amount of acidic etching solution, add a certain amount of iron powder and aluminum sheet successively, carry out two-stage replacement reaction at room temperature for about 3 hours, and obtain a mixed solution of FeCl2 and AlCl3 after filtering;
[0034] As a reference, according to the copper ion content in the acidic etching solution, iron powder with a copper ion content of 1.1 to 1.2 times is added during the first replacement, and the sponge copper is collected after replacement for 7 to 8 hours at 60 to 80°C; aluminum with a copper ion content of 1.1 to 1.2 times is added during the second replacement, and the sponge copper is collected after replacement for 2 to 3 hours, and the remaining filtrate is a mixed solution of FeCl2 and AlCl3. The collected sponge copper is purified by washing, acid washing, etc. to obtain copper blocks. After testing, the copper recovery rate of this scheme is greater than 99%, and the purity of the product sponge copper is greater than 93% (dry basis).
[0035] Step 2: Oxidation: including conventional oxidation and catalytic oxidation;
[0036] The conventional oxidation is to add appropriate amounts of hydrochloric acid and sodium chlorate (or hydrogen peroxide) to the mixed solution at room temperature and under stirring, oxidize the divalent iron ions in the mixed solution into trivalent iron ions, and obtain a reaction solution; the amount of the oxidant added is such that the molar mass ratio of hydrochloric acid to iron is 0.7 to 0.9:1; the amount of sodium chlorate added is such that the molar mass ratio of sodium chlorate to Fe in the mixed solution is 0.7 to 0.9:1; 2+ The molar mass ratio is 0.336:1.
[0037] Catalytic oxidation is to add a catalyst to the mixed solution, introduce oxygen, oxidize the divalent iron ions in the mixed solution into trivalent iron ions, and obtain a reaction solution.
[0038] As an improvement, in the oxidation stage, the present solution also provides a catalytic oxidation device for an acidic etching solution, comprising a cylinder 3, a circulation system connected to the cylinder 3, an ejector 5 connected between the cylinder 3 and the circulation system, and an acceleration reactor connected to the lower part of the ejector 5, wherein the acceleration reactor is located in the cylinder 3. The material of the present device is preferably glass fiber reinforced plastic, which is resistant to high temperature, acid and alkali, has strong pressure bearing capacity, and can also resist fluoride ions in the raw material acid etching solution to prevent internal corrosion of the device.
[0039] like Figure 1 As shown, the circulation system includes a discharge pipe 4 connected to the bottom of the cylinder 3, a circulation pump 1 connected to the discharge pipe 4, a feed pipe 2 connected between the circulation pump 1 and the ejector 5, and an output pipe 18 connected to the feed pipe 2. Multiple circulation pumps 1 can be provided. In this embodiment, two are taken as an example, which are symmetrically arranged on both sides of the cylinder 3. Valves (not shown in the figure) are provided on the feed pipe 2 and the output pipe 18. The circulation pump 1 can extract the liquid material in the cylinder 3 and send it to the ejector 5 from the top of the cylinder 3. When it is injected into the cylinder 3 through the ejector 5, it accelerates the reaction with the reaction gas, and then returns to the cylinder 3 to replenish and accelerate the circulation of the liquid material, thereby accelerating the reaction rate.
[0040] The circulation system also includes graphite heat exchangers, such as Figure 2 As shown, a graphite inlet 21 is provided at the top of the cylinder 3. Figure 1 As shown, a graphite outlet 22 is provided at the bottom of the cylinder 3, and a graphite heat exchanger is connected between the graphite inlet 21 and the graphite outlet 22 (not shown in the figure). The material is pumped into the graphite heat exchanger from the graphite outlet 22 through the graphite heat exchanger pump, and then re-enters the cylinder 3 through the graphite inlet 21, thereby cooling the material for heat exchange and temperature reduction.
[0041] like Figure 3As shown, the ejector 5 is located at the top of the cylinder 3, and an ejector mounting port 10 communicating with the inside of the cylinder 3 is provided on the top of the cylinder 3, and the ejector mounting port 10 is used to fix the ejector 5, and the feed pipe 2 is connected to the ejector 5 from the top, and the mouth of the feed pipe 2 extends into the ejector 5, and a connecting pipe 6 communicating with the inner cavity of the cylinder 3 is provided on the side wall of the ejector 5, and a single-phase air intake valve is provided in the connecting pipe 6, and an accelerating reactor is connected to the bottom of the ejector 5, and the accelerating reactor includes an integrally formed straight pipe and a bent pipe, and an inverted cone pipe is fixed to the straight pipe portion, and the mouth of the inverted cone pipe is in the shape of an inverted cone; a plurality of bent pipes are provided, which are evenly distributed around the straight pipe in a circular direction with the straight pipe as a circle, and the mouth of the bent pipe is upwardly tilted. The liquid material ejected from the ejector 5 is sprayed onto the inner wall of the inverted cone tube, and the shape of the inverted cone tube can once again play a role in collecting and pressurizing the liquid material, so that the liquid material is accelerated to flow out of the ejector 5, so that the gas inside the ejector 5 is quickly rushed out and becomes a negative pressure state, so that the reaction gas in the cylinder 3 can be quickly sucked into the ejector 5 along the connecting pipe 6 to react with the liquid material, thereby accelerating the speed of the reaction gas entering the ejector 5 and improving the reaction efficiency. A bend is set under the straight pipe, so that after the liquid material flows into the straight pipe, it can flow to the pipe mouth along the arc inner wall of the bend. On the one hand, it can improve the smoothness of the liquid material flowing out of the bend, speed up the flow rate of the liquid material, and improve the efficiency; on the other hand, the pipe mouth of the bend is tilted upward, so that the liquid material has an upward trend after being ejected, so that it can have a positive contact with the reaction gas introduced from the top of the cylinder 3, thereby increasing the contact area between the liquid material and the reaction gas, and further improving the reaction rate.
[0042] like Figure 2 As shown, the top of the cylinder 3 is also provided with an auxiliary material hole 9, a liquid alkali and tap water inlet hole 19, an oxygen inlet hole 8, an air intake hole 12, a manhole 7, an observation mirror 13 arranged on the manhole 7, a one-way air intake valve 23, a remote pressure gauge 20, a bursting disc 16, a remote thermometer 14, a pressure relief valve 17, a solid material addition port 15, a liquid material feed port 11 and an exhaust hole 18 located in the middle of the top of the cylinder 3.
[0043] The oxygen inlet 8 is used to introduce the reaction gas into the cylinder 3; the liquid alkali and tap water inlet holes 19 are convenient for pumping liquid alkali and tap water from the outside, the liquid alkali is used to adjust the basicity, and the tap water is used to adjust the iron content according to demand; the one-way suction valve 23 is used to prevent negative pressure from being generated inside the cylinder 3 during discharge to prevent the glass bottle from breaking; the auxiliary material hole 9 is convenient for adding auxiliary materials such as catalysts to increase the reaction plastic, the liquid material feed port 11 is convenient for feeding the liquid material into the cylinder 3, the suction hole 12 is convenient for the reaction gas in the cylinder 3 to enter the ejector 5 and react with the liquid material, thereby accelerating the reaction rate, and the observation mirror 13 is used for the operator to observe the contents of the reactor The remote thermometer 14 is used to monitor the temperature changes in the cylinder 3; the remote pressure gauge 20 is used to monitor the pressure in the cylinder 3; the bursting disc 16 can prevent the pressure in the cylinder 3 from being out of control and burst to form a through hole for forced pressure relief; the pressure relief valve 17 is used to adjust the internal pressure of the cylinder 3 when necessary; the tail gas hole 18 is connected to the tail gas treatment device, which is used to output the tail gas obtained after the reaction in the cylinder 3 to prevent the tail gas from accumulating in the cylinder 3 and affecting the reaction rate; the setting of the manhole 7 makes it convenient for the staff to enter and exit when the cylinder 3 needs maintenance.
[0044] The method of using the catalytic oxidation device is as follows:
[0045] Take the preparation of polyaluminium iron as an example: the raw material is an acidic etching solution that removes copper ions through two-stage replacement. The catalyst is sodium nitrite. The reaction gas is oxygen.
[0046] The working process is as follows:
[0047] ① After the copper ions are removed from the acidic etching solution by two-stage replacement, an acidic etching solution containing iron and aluminum is obtained. The acidic etching solution is injected into the cylinder 3 through the liquid material feed port 11, and the reaction gas is introduced into the cylinder 3 through the oxygen inlet hole 8.
[0048] ② Start the circulation pump 1, pump the liquid material into the ejector 5 through the circulation pump, and then spray it into the cylinder 3 through the ejector 5. A vacuum is formed inside the ejector 5, so that the reaction gas in the cylinder 3 can be sucked into the ejector 5 through the connecting pipe 6 to react with the divalent iron in the acid etching solution and oxidize it into trivalent iron.
[0049] ③ The sodium nitrite solution is injected into the cylinder 3 through the auxiliary material hole 9.
[0050] ④ Open the oxygen valve, and oxygen enters the cylinder 3 from the oxygen inlet hole 8.
[0051] ⑤ Adjust the pressure in the cylinder 3 and control the pressure at 0.02Mpa (optionally 0.02~0.03MPa).
[0052] The pressure control of this scheme is used to ensure the amount of oxygen, that is, the pressure is limited to 0.02-0.03 MPa, which can meet the required amount of oxygen. After the reaction is completed, the pressure continues to rise and no longer drops. After entering the pressure holding state for 5-10 minutes, the divalent iron content is sampled and tested. When the divalent iron content is qualified (that is, when producing polyferric chloride, the ferrous ion content is controlled to be ≤0.2%; when producing ferric chloride, the ferrous ion content is controlled to be ≤0.1%), it means that the oxidation is complete and the reaction can be stopped.
[0053] ⑥ When the temperature inside the cylinder 3 reaches 70-73°C, start the circulating cooling water system to keep the temperature inside the cylinder 3 not exceeding 75°C.
[0054] ⑦React for 3 hours (optionally 3 to 4 hours) to completely oxidize the divalent iron in the acidic etching solution into trivalent iron.
[0055] ⑧Open the valve on the output pipe and the valve of the tail gas hole 18, close the valve of the feed pipe 2, so that the completely oxidized reaction solution is transferred to the product temporary storage tank through the circulation pump 1 for aging for 24 hours, and the tail gas enters the tail gas system through the tail gas hole 18 for treatment and discharge after meeting the standards. After the reaction solution is aged, it is evaporated and concentrated or formulated according to the product index to obtain the water treatment agent and then transferred to the product tank for storage.
[0056] Step 3, post-treatment: After the oxidation is completed, add alkali (including one or more combinations of 30% sodium hydroxide and sodium carbonate) to the reaction solution for alkalization until the alkalinity is 0.5; after aging treatment, liquid polyaluminium ferric chloride PAFC is obtained.
[0057] Example 1
[0058] Take a certain amount of acidic etching solution, add a certain amount of iron powder and aluminum sheet, and carry out two-stage replacement reaction at room temperature for about 3 hours. After filtering, FeC l2 , AlCl3 mixed solution; under room temperature and stirring, add appropriate amount of hydrochloric acid and sodium chlorate to the mixed solution for oxidation; after the oxidation is completed, add 30% sodium hydroxide (sodium carbonate) as needed for alkalization until the alkalinity is 0.5, and after treatment, polymerization treatment and aging treatment, liquid polyaluminum ferric chloride PAFC is obtained.
[0059] Comparative Example 1
[0060] This comparative example is basically the same as Example 1, except that in the oxidation stage, appropriate amounts of sulfuric acid and hydrogen peroxide are added to the mixed solution under room temperature and stirring for oxidation.
[0061] Comparative Example 2
[0062] This comparative example is basically the same as Example 1, except that in the oxidation stage, in the catalytic oxidation device, appropriate amounts of hydrochloric acid, catalyst sodium nitrite and oxygen are added to the mixed solution, and the temperature is increased to perform catalytic oxidation.
[0063] The amounts of reagents used in preparing poly-iron-aluminum from acidic etching solutions in Example 1 and Comparative Examples 1-2 of this scheme are detailed in Table 2. Table 1 shows the source and composition of the treated acidic etching solution. The PAFC prepared is as follows: Figure 4 The test data are shown in Table 3.
[0064] Table 1 Acid etching solution test index data
[0065] index Cu / % <![CDATA[H + / mol / L]]> Salt / mg / L Data (Founder) 9.3 3.31 <![CDATA[3.86*10 5 ]]> Data (Sichuan Billion) 10.62 4.47 /
[0066] Table 2 Preparation of polyaluminium ferric chloride experimental record
[0067]
[0068] Table 3 Preparation of polyaluminium ferric chloride test data
[0069]
[0070] Experimental data show that the polyaluminum chloride ferric water treatment agent that basically meets the liquid product indicators in "HG / T5359-2018 Water Treatment Agent Polyaluminum Chloride Ferric" can be prepared by treating acidic etching solutions from different sources using this scheme, thereby realizing the resource recycling of acidic etching solutions.
[0071] Specifically, the experiment shows that the two-stage replacement of aluminum and iron can fully recover copper ions in the acidic etching solution, the copper recovery rate is greater than 99%, and the purity of the product sponge copper is greater than 93% (dry basis) (the sponge copper data shown in Table 2 is the sponge copper collected after the replacement, which contains water and salt and needs to absorb water). The aluminum-iron ratio and alkalinity in the reaction process significantly affect the hydrolysis and polymerization of PAFC. When the aluminum-iron ratio is 2:1, a large amount of solid is produced without alkalinization of PAFC to form a suspension, and there is stratification after standing for a long time. As the aluminum-iron ratio increases to 3:1, 4.5-5.5:1, the turbidity of PAFC gradually disappears, and the higher the iron content, the lower the alkalinity at which turbidity occurs. The increase in alkalinity causes PAFC to gradually produce solids and become turbid. The turbidity of PAFC (2) and PAFC (3) is caused by excessive alkalinity. The hydrolysis polymerization process is slow, so the alkalizer needs to be added slowly to avoid adding too much and causing turbidity. The oxidation process uses hydrochloric acid + sodium chlorate and sulfuric acid + hydrogen peroxide, both of which have good oxidation effects. The color of sodium chlorate oxidation is darker.
[0072] The PAFC alumina, total iron, divalent iron, arsenic, lead, cadmium, chromium, zinc, nickel, pH (PAFC (3)), density (PAFC (2), PAFC (3)) indicators obtained in the experiment all meet the "HG / T 5359-2018 Water Treatment Agent Polyaluminium Ferric Chloride" standard. The basicity, mercury and alumina in the indicators do not meet the detection conditions. The alumina content is calculated based on the aluminum and iron contents. The ferrous ion detection is easily disturbed during sodium chlorate oxidation. The turbid appearance of PAFC (1) contains a large amount of solids due to excessive iron content and the appearance of low polymers. It can be adjusted by adding aluminum and hydrochloric acid for re-oxidation to obtain a product that meets the HG / T5359-2018 standard. The turbid appearance of PAFC (2, 3) is caused by excessive alkali addition during the alkalization process. Reducing the amount of alkali added or increasing the acid to adjust the basicity to 5-20 can effectively improve it. It can be seen from this that
[0073] Experimental Example 1: Polyaluminium Ferric Chloride Flocculation Experiment
[0074] Take PAFC (1) and dilute it at 1:1.5 for later use. Take the prepared suspension, take the waste emulsion from the workshop and the wastewater from the sewage regulating tank, add 0.5 ml of PAFC dilution to each, adjust the pH to about 7-8 with 30% sodium hydroxide solution, mix well and let it stand. Figure 5 :
[0075] Take the prepared suspension and workshop waste paint water, add quantitative PAFC (2) and PAFC (3) solutions respectively, use 30% sodium hydroxide solution to adjust the pH to about 6-9, mix well and let stand. The experimental results are recorded in Table 4. The experimental phenomena are as follows Figure 6 and Figure 7 :
[0076] Table 4 PAFC flocculation experiment record
[0077]
[0078]
[0079] Experimental data show that PAFC (1), PAFC (2) and PAFC (3) prepared by this scheme have good flocculation effect when applied to the preparation of suspension, waste emulsion, sewage from regulating tank and waste paint water. The flocs of the prepared suspension and sewage from regulating tank are compact and have fast sedimentation speed, while the sedimentation speed of waste emulsion and waste paint water is relatively slow. The higher the aluminum content in PAFC, the better the flocculation and sedimentation effect.
[0080] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.
Claims
1. A method for preparing polymerized iron aluminum from an acidic etching solution, characterized in that: The steps include: Step 1, two-stage replacement: aluminum and iron are added to the acidic etching solution in batches to perform two-stage replacement of copper ions in the acidic etching solution to obtain a mixed solution of sponge copper and ferrous chloride and aluminum chloride; Step 2, catalytic oxidation: adding a catalyst to the mixed solution, introducing oxygen, oxidizing the divalent iron ions in the mixed solution into trivalent iron ions, and obtaining a reaction solution; Step 3, post-treatment: The reaction solution is subjected to aging treatment to obtain liquid polyaluminium ferric chloride PAFC.
2. The method for preparing polymerized iron aluminum from an acidic etching solution according to claim 1, characterized in that: As an improvement, in step one, the two-stage replacement is as follows: according to the copper ion content in the acidic etching solution, iron powder with a copper ion content of 1.1 to 1.2 times is added during the first-stage replacement, and after the addition is completed, the sponge copper is collected after the replacement is carried out at 60 to 80° C. for 7 to 8 hours; aluminum with a copper ion content of 1.1 to 1.2 times is added during the second-stage replacement, and after the addition is completed, the sponge copper is collected after the replacement is carried out for 2 to 3 hours, and the remaining filtrate is a mixed solution of FeCl2 and AlCl3.
3. A method for preparing polymerized iron aluminum from an acidic etching solution according to claim 2, characterized in that: During the two-stage replacement process, the amount of iron powder and aluminum flakes added is such that the molar mass ratio of Fe to Al in the mixed solution after replacement is 4.5 to 5.5:
1.
4. The method for preparing polymerized iron aluminum from an acidic etching solution according to claim 1, characterized in that: In step 2, the catalyst is sodium nitrite, and the amount of the catalyst added is 3‰; the oxidant is oxygen.
5. The method for preparing polymerized iron aluminum from an acidic etching solution according to claim 4, characterized in that: The pressure of the catalytic oxidation is 0.02-0.03 MPa, the temperature is controlled within 75° C., and the reaction time is 3-4 hours.
6. The method for preparing polymerized iron aluminum from an acidic etching solution according to claim 1, characterized in that: In step 2, the catalytic oxidation can also be replaced by conventional oxidation, wherein the conventional oxidation is to add hydrochloric acid to the mixed solution under stirring at room temperature to adjust the free acid and Cl-Fe ratio of the mixed solution, add sodium chlorate or hydrogen peroxide as an oxidant, oxidize the divalent iron ions in the mixed solution into trivalent iron ions, and obtain a reaction solution.
7. The method for preparing polymerized iron aluminum from an acidic etching solution according to claim 6, characterized in that: The amount of hydrochloric acid added is such that the molar mass ratio of Cl to Fe in the mixed solution is 0.7 to 0.9:
1.
8. The method for preparing polymerized iron aluminum from an acidic etching solution according to claim 7, characterized in that: The amount of sodium chlorate added is such that the sodium chlorate and Fe 2+ The molar mass ratio is 0.336:1.
Citation Information
Patent Citations
Method for recycling copper from acid copper chloride etching liquid
CN101899665A
Method for recycling acidic copper-etching waste solution
CN102912352A
Precipitant for recycling acidic etching waste liquid, and processing method thereof
CN104313583A
Method for extracting copper from acidic etching waste liquid
CN114703377A